“Comparación in vitro de la eficacia disolvente del aceite Citrus Aurantifolia frente al Citrus Sinensis sobre la gutapercha endodóntica” - Menor Arteaga, Javier Wilson (2019)
ABSTRACT Purpose: To compare in vitro the solvent efficiency of Citrus Aurantifolia oil with Citrus Sinensis on endodontic gutta-percha. Methods: 270 copper cylinders were used, which were filled with endodontic gutta-percha using the manual technique, dividing into three groups of 90 for each solvent; Citrus Aurantifolia, Citrus Sinensis and physiological saline, of which of each group was subdivided into three groups of 30 at 2, 5 and 10 minutes that were weighed on the analytical balance before and after being submerged in the Petri dish with the solvents, each cylinder was submerged only once per time. Results: Citrus Aurantifolia oil showed no superiority in dissolution in comparison with Citrus Sinensis oil, there was a significant difference of (p <0.01) and no effect of physiological saline was found on gutta-percha. Conclusion: Citrus Aurantifolia oil showed statistically lower dissolution capacity than Citrus Sinensis.